Back Cover: Design, Synthesis, and Chemistry of Bis(σ)borate and Agostic Complexes of Group 7 Metals (Chem. Eur. J. 41/2017). Issue 41 (9th June 2017) - Saha, Koushik; Ramalakshmi, Rongala; Gomosta, Suman; Pathak, Kriti; Dorcet, Vincent; Roisnel, Thierry; Halet, Jean‐François; Ghosh, Sundargopal
Abstract : The lability of the CO ligands of manganese bis(σ)borate complex, [Mn(CO)3 (μ‐H)2 HB(NCSC6 H4 )NR] (R=NCSC6 H4 ) was studied with different phosphine ligands. Treatment of this Mn‐bis(σ)borate complex with PPh3 led to the formation of two manganese bis(σ)borate complexes, [(PPh3 )(CO)2 Mn(μ‐H)2 HB(NCSC6 H4 )NR] and [(PPh3 )(CO)2 Mn(μ‐H)2 HBNR(NCSC6 H4 )] (R=NCSC6 H4 ), as structural isomers having two different arrangements of the bis(benzothiazol‐2‐yl)amine ligand around the central metal atom. More information can be found in the Full Paper by S. Ghosh et al. onpage 9812 .